Answer :

P(AB)=









6P(A)2–5P(A)+1=0


6P(A)2–3P(A)–2P(A)+1=0


[2P(A)–1][3P(A)–1]=0


2P(A)–1=0


2P(A)=1



3P(A)–1=0


3P(A)=1




Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Coloured balls arMathematics - Board Papers

If A and B are twMathematics - Board Papers

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

Prove that if E aMathematics - Board Papers

State True or FalMathematics - Exemplar